Whole child education - Miller, John P., 1943- (Toronto : University Of Toronto Press, 2012)
Public education is often viewed as dominated by an emphasis on test scores and narrowly defined parameters of performance and achievement. By contrast, John P. Miller'sWhole Child Education fosters relationships between various forms of thinking, links body and mind, and recognizes the inner life of the child. Addressing issues of teaching, curriculum, the school, and teacher wellness, Miller presents three basic approaches (transmission, transaction, and transformation) that facilitate a connection with the whole student. Practical examples from teachers who have incorporated Miller's ideas into their own classrooms and description of Toronto's Whole Child School (founded in 2009) illustrate how the 'Whole Curriculum' can be implemented on both the small and large scale. Inspired by the powerful vision of Martin Luther King and his concept of the Beloved Community, Whole Child Education is a vehicle for building community through holistic education.